Level of fidelity of the film adaptation of Percy Jackson - De los Reyes, Rozel A.
This research is an assessment of the level of fidelity of the film adaptation of Percy Jackson and the Sea of Monsters. It compares the manifest content of the novel and film adaptations in terms of plot, character and setting. The analysis of data uses the standards set by Desmond and Hawkes (2006) in evaluating the type of film adaptation, which is either loose, intermediate, or close. The research shows the film adaptation of Percy Jackson and the Sea of Monsters as an intermediate adaptation with an overall fidelity of 36.16% which means that some of the elements of the story are kept in the film, others are dropped and still some elements are added. This study would be beneficial especially to fans and film reviewers in analyzing other film adaptations.